Vacuolar-ATPase-mediated intracellular sequestration of ellipticine contributes to drug resistance in neuroblastoma cells - Hrabeta, Jan; Groh, Tomas; Khalil, Mohamed Ashraf; Poljakova, Jitka; Adam, Vojtech; Kizek, Rene; Uhlik, Jiri; Doktorova, Helena; Cerna, Tereza; Frei, Eva; Stiborova, Marie; Eckschlager, Tomas (International journal of oncology, 2015)
Neuroblastoma is the most common cancer in infants and the fourth most common cancer in children. Aggressive cell growth and chemoresistance are notorious obstacles in neuroblastoma therapy. Exposure to the anticancer drug ellipticine inhibits efficiently growth of neuroblastoma cells and induces apoptosis in these cells. However, ellipticine induced resistance in these cells. The upregulation of a vacuolar (V)-ATPase gene is one of the factors associated with resistance development. In accordance with this finding, we found that levels of V-ATPase protein expression are higher in the ellipticine-resistant UKF-NB-4ELLI line than in the parental ellipticine-sensitive UKF-NB-4 cell line. Treatment of ellipticine-sensitive UKF-NB-4 and ellipticine-resistant UKF-NB-4ELLI cells with ellipticine-induced cytoplasmic vacuolization and ellipticine is concentrated in these vacuoles. Confocal microscopy and staining of the cells with a lysosomal marker suggested these vacuoles as lysosomes. Transmission electron microscopy and no effect of an autophagy inhibitor wortmannin ruled out autophagy. Pretreatment with a V-ATPase inhibitor bafilomycin A and/or the lysosomotropic drug chloroquine prior to ellipticine enhanced the ellipticine‑mediated apoptosis and decreased ellipticine-resistance in UKF-NB-4ELLI cells. Moreover, pretreatment with these inhibitors increased formation of ellipticine-derived DNA adducts, one of the most important DNA-damaging mechanisms responsible for ellipticine cytotoxicity. In conclusion, resistance to ellipticine in the tested neuroblastoma cells is associated with V-ATPase-mediated vacuolar trapping of this drug, which may be decreased by bafilomycin A and/or chloroquine.
Keywords: chlorochin; Macrolides; Humans; neuroblastom; elipticiny; Antineoplastic Agents; lidé; chemorezistence; vakuolární protonové ATPasy; apoptóza; vakuoly; Chloroquine; nádorové buněčné linie; protinádorové látky; Neuroblastoma; Ellipticines; Cell Line, Tumor; makrolidy; Vacuoles; Vacuolar Proton-Translocating ATPases; adukty DNA; DNA Adducts; Drug Resistance, Neoplasm; Apoptosis